Knowledge of BRCA gene among young Pakistani adults: a short report - Shahir Muhammad Ibne Rasa; Daler Ahmad; Mishaal Hasan; Agha Hashim Raza Khan; Minahil Farhan; Farzad Effan (Journal of the Pakistan Medical Association, 2024)
A total of 271 young Pakistani adults responded to a self-designed multiple choice-based questionnaire (Alpha = 0.83) which was then used to assess the levels of knowledge regarding breast cancer susceptibility (BRCA) gene mutation. Overall knowledge levels were assessed using the sum score of each response; any possible significance between knowledge scores and educational backgrounds as well as gender were also tested. The results show that 63.8% of the sample population had awareness about BRCA gene mutation. Knowledge scores were comparable across both groups (medical and non-medical educational backgrounds) with 13.8% of medical and 13.5% of non-medical respondents demonstrating a high level of knowledge about the BRCA gene mutation and its testing. Neither gender nor educational background had a significant influence on knowledge scores. The results from this report suggest that awareness regarding BRCA gene was adequate, while knowledge levels were noted to be poor among the sample population. Keywords: Breast cancer, Pakistan, Awareness, Knowledge, Gene.